Columnar Mesophases and Organogels Formed by H-Bound Dimers Based on 3,6-Terminally Difunctionalized Triphenylenes - Nahir Vadra; Lisandro J. Giovanetti; Pablo H. Di Chenna; Fabio D. Cukiernik (Gels)
A series of triphenylene (TP) compounds—denoted 3,6-THTP-DiCnOH—bearing four hexyloxy ancillary chains and two variable-length alkoxy chains terminally functionalized with hydroxyl groups have been synthesized and characterized. The shorter homologs revealed mesogenic characteristics, giving rise to thermotropic mesophases in which π-stacked columns of H-bound dimers self-organize yielding superstructures. Molecular-scale models are proposed to account for their structural features. The three studied compounds yielded supramolecular gels in methanol; their ability to gelify higher alcohols was found to be enhanced by the presence of water. The intermediate homolog also gelled n-hexane. Compared to their isomeric 2,7-THTP-DiCnOH analogs, the 3,6-derivatives showed a higher tendency to give rise to LC phases (wider thermal ranges) and a lower organogelling ability (variety of gelled solvents, lower gels stabilities). The overall results are analyzed in terms of different kinds of competing H-bonds: intramolecular, face-to-face dimeric, lateral polymeric, and solvent–TP interactions.